Willingness to pay for dental check-ups and the associated socioeconomic factors among Japanese adults with fewer than 20 remaining teeth: a cross-sectional study - Katsuo Oshima; Moeka Araki; Rika Takei; Yasushi Kumono; Ryutaro Kobayashi; Tomoko Tanaka; Masaomi Fukuda (BMC Health Services Research)
Abstract Background For patients with a reduced number of remaining teeth, receiving dental check-ups regularly is important to continue oral health maintenance. However, few studies have evaluated the willingness to pay (WTP) for dental check-ups among those with a reduced number of teeth. We determined the WTP for dental check-ups and investigated the socioeconomic factors associated with high and low WTP among Japanese adults with < 20 remaining teeth, based on whether they have dental check-ups on a routine basis. Methods We conducted a cross-sectional study using a web-based survey in March 2024. Overall, 830 study participants (men and women aged 50–74 years) with 1–19 remaining teeth were randomly sampled from the registrants of an online research company in Japan. The participants were categorized into two groups: those who had (DCR group, 445 participants) and those who had not undergone dental check-ups regularly (non-DCR group, 385 participants). After excluding protest zero responses, the WTP values for dental check-ups in each group were calculated and compared. A negative binomial regression model was used to evaluate the factors associated with high and low WTP values. Results The sample for analysis included 442 and 378 participants in the DCR and non-DCR groups, respectively. The median (mean) WTP values for dental check-ups were 3,000 (3,559) Japanese Yen (JPY) and 2,000 (2,778) JPY in the DCR and non-DCR groups, respectively. Multivariate analysis indicated that in the DCR group, living in the urban area (prevalence ratio [95% confidence intervals]: 1.23 [1.06–1.43]) statistically significantly positively predicted WTP values. For the non-DCR group, a household income of 2–4 (1.48 [1.09–2.00]), 6–8 (1.50 [1.03–2.20]), and > 8 million JPY (1.47 [1.00–2.16]) statistically significantly positively predicted WTP values. Conclusions Those with a reduced number of remaining teeth and who did not undergo dental check-ups regularly expressed a lower WTP for dental check-ups. This factor was positively correlated with household income. To encourage dental service utilization among these individuals, policies that institutionalize regular dental check-ups with reduced co-payments will need to be implemented.